Exploring metabolic dynamics during the fermentation of sea buckthorn beverage: comparative analysis of volatile aroma compounds and non-volatile metabolites using GC–MS and UHPLC–MS - Peng, Bo; Li, Jingjing; Shan, Chunhui; Cai, Wenchao; Zhang, Qin; Zhao, Xinxin; Li, Shi; Wen, Jing; Jiang, Lin; Yang, Xinquan; Tang, Fengxian (Frontiers in Nutrition, 2023)
Sea buckthorn has a high nutritional value, but its sour taste and foul odor make it unpalatable for consumers. In this study, we analyzed the metabolite changes occurring during the yeast-assisted fermentation of sea buckthorn juice using the HeadSpace Solid-Phase Microextraction Gas Chromatography-Mass Spectrometry (HS-SPME-GC-MS) and Ultra-High Performance Liquid Chromatography-Mass Spectrometry (UHPLC-MS) techniques. A total of 86 volatile aroma compounds were identified during the fermentation process. The content of total volatiles in sea buckthorn juice increased by 3469.16 μg/L after 18 h of fermentation, with 22 compounds showing elevated levels. Notably, the total content of esters with fruity, floral, and sweet aromas increased by 1957.09 μg/L. We identified 379 non-volatile metabolites and observed significant increases in the relative abundance of key active ingredients during fermentation: glycerophosphorylcholine (1.54-fold increase), glutathione (1.49-fold increase), L-glutamic acid (2.46-fold increase), and vanillin (0.19-fold increase). KEGG pathway analysis revealed that amino acid metabolism and lipid metabolism were the primary metabolic pathways involved during fermentation by Saccharomyces cerevisiae. Fermentation has been shown to improve the flavor of sea buckthorn juice and increase the relative content of bioactive compounds. This study provides novel insights into the metabolic dynamics of sea buckthorn juice following yeast fermentation through metabolomics analysis. These findings could serve as a theoretical foundation for further studies on the factors influencing differences in yeast fermentation.